Investigating the role of Corona stress mediators in relationship between internet addiction and marital and family conflict and violence - Hadi Salimi; kobra Hajializade; Mojtaba Ameri Siahoui; Parisa Behdost (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2021)
COVID-19 creates stressful conditions and can affect marital and family relationships. Therefore this study was done aimed to investigate the role of Corona stress (CS) mediators in relationship between internet addiction (IA) and marital and family conflict and violence (MCV, FCV). The method of this study was descriptive and path analysis. The statistical population included all residents of Bandar Abbas in 2020, that 421 subject were selected using Random sampling method and were divided into married groups (229) and single (192). The data were collected online. Corona Stress Scale (CSS-18), Marital and Family Conflict and Violence Questionnaire and Internet Addiction Test (IAT) were used for gathering data. Data Analyzing was conducted with Pearson correlation, multiple regression, and path analysis and also SPSS-22 software and the Preacher and Hayes macro program. The results of the data analysis showed that IA and CS can explain 26.5% of MCV variance and 19.1% of FCV variance. IA can also explain 19.4% of CS variance in group of married people and 13.6% in group of single people. Also, the results of indirect effects showed that IA through CS has a 7.4% effect on MCV and 12.2% has an indirect effect on FCV. According to the findings of this study, the harmful use of the internet during the Corona period causes people to experience a level of stress, and this stress can enter the marital and family boundaries, resulting in marital and family conflicts and violence.